Foot and ankle disorders : an illustrated reference - Jung, Hong-Geun (Springer, 2016)
This book, specifically designed to be of value in clinical practice, is an up-to-date, case-oriented reference on the various common foot and ankle disorders that is presented in the style of a teaching file, with a wealth of informative illustrations. The text is concise and informative, providing a general overview of each disorder, identifying key points for correct diagnosis and differential diagnosis, and highlighting tips and pitfalls in conservative and operative treatment. The most important feature, however, is the depiction of representative cases by means of detailed, high-quality color photographs that will acquaint the reader with the key appearances relevant to diagnosis and treatment.
Keywords: Foot : Diseases; Ankle : Diseases; jalat; nilkat; sairaudet; vammat; kipu; leikkaushoito; ortopedia; diabetes; nivelreuma; kuntoutus; jalkaterapia